Библия рядового: семикнижие / П. Любомиров ; [художник Ю. А. Наговицын] - Любомиров Петр Петрович (Удмуртия, 1995)
Экземпляры: ф.23 (1998) / Инвентарный номер: 40788 / Цена: / Сис.шифр: 84(2Рос=Удм)6 / Авт.знак: Л 93 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6